Regional trading arrangements among developing countries: the ASEAN example - DeRosa, Dean A. (International Food Policy Research Institute, 1995)
In Regional Trading Arrangements among Developing Countries: The ASEAN Example, Research Report 103, Dean A. DeRosa examines the experiences of the Association of Southeast Asian Nations (ASEAN) with regional investment and trade arrangements and presents a quantitative analysis of the economic implications of the new ASEAN Free Trade Area (AFTA). The report focuses on the new trading area's potential for significantly reducing trade and macroeconomic policy-related disincentives to greater agricultural production and trade by the ASEAN countries, compared with an alternative policy of broader trade liberalization.